"I like computers. I hate coding": a portrait of two teens' experiences. Issue 5 (13th May 2019) - Haduong, Paulina
Abstract : Purpose: Some empirical evidence suggests that historically marginalized young people may enter introductory programming experiences with skepticism or reluctance, because of negative perceptions of the computing field. This paper aims to explore how learner identity and motivation can affect their experiences in an introductory computer science (CS) experience, particularly for young people who have some prior experience with computing. In this program, learners were asked to develop digital media artifacts about civic issues using Scratch, a block-based programming language. Design/methodology/approach: Through participant observation as a teacher and designer of the course, artifact analysis of student-generated computer programs and design journals, as well as with two follow-up 1-h interviews, the author used the qualitative method of portraiture to examine how two reluctant learners experienced a six-week introductory CS program. Findings: These learners' experiences illuminate the ways in which identity, community and competence can play a role in supporting learner motivation in CS education experiences. Research limitations/implications: As more students have multiple introductory computing encounters, educators need to take into account not only their perceptions of the computing field more broadly but also specific prior encounters with programming. Because of the chosen research approach, the research results may lack generalizability. Researchers are encouraged to explore other contexts and examples further. Practical implications: This portrait highlights the need for researchers and educators to take into account student motivation in the design of learning environments. Originality/value: This portrait offers a novel examination of novice programmer experiences through the choice in method, as well as new examples of how learner identity can affect student motivation.